2019
DOI: 10.1108/jap-06-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

The employment conditions of social care personal assistants in England

Abstract: Purpose The purpose of this paper is to describe the employment conditions of social care personal assistants (PAs) in England. In England, disabled adults have been able to directly employ people to meet their care or support needs for a number of years, little is known about the employment conditions of people who are directly employed. Design/methodology/approach PAs were recruited mainly through third sector and user led organisations. A total of 105 social care PAs took part in a semi-structured telepho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 14 publications
4
19
0
Order By: Relevance
“…Overall little is known about these employers’ views on deciding whether to undertake DBS checks and responses to any disclosures (ibid). A recent study of PAs’ views (Woolham et al , 2019b) found that, while the vast majority thought that such checks would be appropriate, there was no requirement to undertake them. Interviews with wider stakeholders revealed varied opinions about whether such checks were appropriate in all cases, especially given the existing close relationship between some PAs and their employers.…”
Section: Resultsmentioning
confidence: 99%
“…Overall little is known about these employers’ views on deciding whether to undertake DBS checks and responses to any disclosures (ibid). A recent study of PAs’ views (Woolham et al , 2019b) found that, while the vast majority thought that such checks would be appropriate, there was no requirement to undertake them. Interviews with wider stakeholders revealed varied opinions about whether such checks were appropriate in all cases, especially given the existing close relationship between some PAs and their employers.…”
Section: Resultsmentioning
confidence: 99%
“…Personal Assistants) in England reflects this desire among clients, families and homecare workers. These workers value the variety of their work and opportunities to adjust to the client’s needs and their relationships ( Woolham et al, 2019 ), beyond the constraints of a care plan.…”
Section: Discussionmentioning
confidence: 99%
“…If the third party employing PAs is a traditional care provider, without a genuine commitment to independent living, then the PA relationship will likely resemble paternalistic models of care, in which the disabled person lacks genuine choice and control. There are some indications that the latter of these employment arrangements are becoming increasingly common in the UK (Woolham et al, 2019), and future research must consider the implications this has for PA as a distinct form of care work.…”
Section: Discussionmentioning
confidence: 99%